2006
DOI: 10.1111/j.1365-2710.2006.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of oral antidiabetic drugs by outpatients in Taiwan: 1997-2003

Abstract: The prescribing rates of OADs are shifting from the older OADs (i.e. SUs) to newer OADs [i.e. alpha-glucosidase inhibitor (AGI), MGs, and TZDs]. The prescribing patterns of OADs are moving toward combination therapy, especially triple oral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(37 reference statements)
5
16
1
Order By: Relevance
“…This higher prevalence of DM among elderly patients is in accordance with studies from India [8,9] and Taiwan [10]. Prevalence was slightly The results are in conformity with DECODA study group [11] and a previous study in south India [12].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This higher prevalence of DM among elderly patients is in accordance with studies from India [8,9] and Taiwan [10]. Prevalence was slightly The results are in conformity with DECODA study group [11] and a previous study in south India [12].…”
Section: Discussionsupporting
confidence: 95%
“…Hence metformin is currently the most frequently used oral agent to treat type 2 DM and is generally accepted as the first-line treatment for this illness [13,27,31,32]. Among the antidiabetics in our study, metformin was indeed the most frequently prescribed oral drug in monotherapy as well as in combination which is justified (Table 4) even though some studies from overseas [10,23] and India [12,33] have reported sulfonylureas as the most frequently prescribed oral antidiabetic drugs. This dissimilarity can be due to the physician's choice related to the type of patients, their coexistent illnesses, cost and availability of medicines.…”
Section: Discussionmentioning
confidence: 66%
“…7,11,15,16,[18][19][20] Among the sulfonylureas, glimepiride was the most commonly prescribed drug along with metformin which is similar to studies. 10,18 Metformin is one of the safest and most cost effective drug compared to other drugs in terms of hypoglycaemia and decreasing BMI, hence this could be the most probable reason for this finding.…”
Section: Discussionsupporting
confidence: 51%
“…28 Metformin is the therapy of choice for overweight and obese patients with type 2 diabetes. 29 Metformin acts as a peripheral sensitizer of insulin and also has beneficial effects on insulin resistance, an important factor in the pathogenesis of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%